Reflections in Place : Connected Lives of Navajo Women - Deyhle, Donna (Book collections on Project MUSE., 2009)
Draws on the experiences of three Navajo women seeking an education in southeastern Utah to reveal the devastating consequences of racial stereotyping in society and in the educational system.